INTEGRATIVE CURRICULUM OF RELIGION AND SCIENCE AT SPECIAL PESANTREN FOR UNIVERSITY STUDENTS - Ali, Nur (ULUL ALBAB Jurnal Studi Islam, 2019)
This article describes the development of the integration of religion and science in Islamic higher education institutions in Indonesia. The focus of this discussion is the integrated religion and science curriculum at special pesantren (Islamic boarding school) for university students. The aim is to find the implementation of the model of the integrative curriculum of religion and science at special pesantren for university students (hereafter referred to as PESMA). This study uses the constant comparative method. This article concludes that the integrative curriculum of PESMA of UIN Maulana Malik Ibrahim Malang is currently a new model in Indonesia. The model of THE integrative curriculum of PESMA of UIN (State Islamic University) is different than that of other PESMA in Indonesia. The development of the curriculum was triggered by the conversion of IAIN (State Islamic Institute) to UIN, and the development of general study programs at the university. This factor can complement the model of the integrative curriculum at Islamic higher education institutions and become an integration laboratory in Indonesia, according to Azyumardi Azra, Amin Abdullah, and Salahuddin Wahid.